PENGAJARAN PENDIDIKAN AGAMA KRISTEN TENTANG KARUNIA BAHASA ROH DALAM 1 KORINTUS 12:8-10 DI GPDI EFRATA DEPOK - Sihite, Jelita; Hizkia Chrisman El-Shaddai (STT IKSM SANTOSA ASIH, 2025)
In contemporary churches, misunderstandings regarding spiritual gifts often occur, where supernatural phenomena are frequently emphasized over Biblical truth, alongside a tendency for congregations to prioritize specific gifts such as healing. This study aims to provide a correct theological understanding of spiritual gifts according to the Apostle Paul's teaching in 1 Corinthians 12:8-10, to establish correct theology within the congregation. The method used in this research is qualitative with a library research approach, collecting and analyzing information from relevant written sources. The results show that the word